2017
DOI: 10.1111/mice.12286
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Dimension Dynamic Bayesian Network for Large‐Scale Degradation Modeling with an Application to a Bridges Network

Abstract: Modelling the stochastic evolution of a largescale fleet or network generally proves to be challenging due to the large number of variables and their interactions. This difficulty may be compounded through complex relationships between various assets in the network. Although a great number of probabilistic graph-based models (e.g., Bayesian networks) have been developed recently to describe the behaviour of single assets, one can find significantly fewer approaches addressing a fully integrated network. An ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Different application of NPBNs based on the normal copula assumption can be found in the scientific literature, (e.g. Morales-Nápoles et al, 2014a;Jesionek and Cooke, 2007;Hanea and Ale, 2009;Kosgodagan-Dalla Torre et al, 2017). In reliability studies, Morales-Nápoles and Steenbergen (2014) implemented NPBNs for modelling complex traffic systems and showed that they can be used for computing design values for individual axles, vehicle weight, and maximum bending moments of bridges within certain time intervals.…”
Section: Nonparamentric Bayesian Networkmentioning
confidence: 99%
“…Different application of NPBNs based on the normal copula assumption can be found in the scientific literature, (e.g. Morales-Nápoles et al, 2014a;Jesionek and Cooke, 2007;Hanea and Ale, 2009;Kosgodagan-Dalla Torre et al, 2017). In reliability studies, Morales-Nápoles and Steenbergen (2014) implemented NPBNs for modelling complex traffic systems and showed that they can be used for computing design values for individual axles, vehicle weight, and maximum bending moments of bridges within certain time intervals.…”
Section: Nonparamentric Bayesian Networkmentioning
confidence: 99%
“…A few studies that account for the relationships between elements are available in the literature [33,34]. The fault tree and impact tree methods have been used to analyze how one element affects the other elements [35][36][37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…LMDP aims to either minimize total managing costs or maximize asset performance over finite/infinite planning horizon. A lot of efforts have been made to further refine LMDP method since it was first proposed (Durango‐Cohen and Madanat, ; Kosgodagan‐Dalla Torre et al., ; Mishalani and Gong, ; Smilowitz and Madanat, ). Smilowitz and Madanat () extended LMDP model to a network‐level problem by including network‐level constraints, for example, minimum/maximum percentage of assets allowed in certain condition, minimum/maximum yearly budget.…”
Section: Literature Reviewmentioning
confidence: 99%